INDY—A New Link to Metabolic Regulation in Animals and Humans - Blanka Rogina (Frontiers in Genetics, 2017)
The Indy (I’m Not Dead Yet) gene encodes the fly homolog of the mammalian SLC13A5 citrate transporter. Reduced expression of the Indy gene in flies and worms extends their longevity. INDY is expressed in the plasma membrane of metabolically active tissues. Decreased expression of Indy in worms, flies, mice, and rats alters metabolism in a manner similar to calorie restriction. Reducing INDY activity prevents weight gain in flies, worms, and mice, and counteracts the negative effects of age or a high fat diet on metabolism and insulin sensitivity. The metabolic effects of reducing INDY activity are the result of reduced cytoplasmic citrate. Citrate is a key metabolite and has a central role in energy status of the cell by effecting lipid and carbohydrate metabolism and energy production. Thereby newly described drugs that reduce INDY transporting activity increase insulin sensitivity and reduce hepatic lipid levels via its effect on hepatic citrate uptake. A recent report presented the first direct link between increased hepatic levels of human INDY, insulin resistance, and non-alcoholic fatty liver disease in obese humans. Similarly increased hepatic mIndy levels were observed in non-human primates fed on a high fat diet for 2 years. This effect is mediated via the stimulatory effect of the interleukin-6/Stat3 pathway on mINDY hepatic expression. These findings make INDY a potential and very promising target for the treatment of metabolic disorders in humans.